Penerapan Algoritme Finite State Machine Pada Game "Si Jampang" Berbasis Android - Ar-Rijalul Haq; Mardi Hardjianto (Bit (Fakultas Teknologi Informasi Universitas Budi Luhur), 2022)
The development of technology today is much faster than in previous years, the transformation of past technology into technology that is easier and faster, especially games. Game is a means of entertainment with the aim of having fun and filling spare time. Games can be a unique learning process for the community, because they will not only gain knowledge about folklore but they will also feel entertained. By making this game, it is hoped that it can help educate children to get to know and increase their knowledge about Indonesian folklore. Aside from being an entertainment medium to relieve fatigue or fill spare time, games can also be used as an attractive delivery medium for the younger generation, especially young people. This game is a door for the younger generation, especially young people, to get to know the character of warriors in Indonesia. The design of this android game entitled Si Jampang was made to provide an introduction to the character of Si Jampang and can provide entertainment to anyone who plays it. The development of foreign media and culture that has spread widely, it is feared that if the Si Jampang character is not maintained, then this one character will be forgotten. It is very unfortunate if the character of Si Jampang is swallowed up by the times, so precautions must be taken so that the character of Si Jampang is not completely forgotten. Namely by using the media game. For this reason, this android game was created as a problem solution for the author to be a deterrent so that this problem does not actually happen, but also can provide entertainment to users, so that they are interested in playing this android game. This game is a 2D game based on android. This game will be implemented by artificial intelligence using the Finite State Machine method. The method will regulate the behavior of the object when a change in the state or condition of the game occurs